A promising CuOx/WO3 p-n heterojunction thin-film photocathode fabricated by magnetron reactive sputtering. (8th February 2019) - Xie, Tian; Zheng, Tao; Wang, Ruiling; Pu, Taofei; Li, Xiaobo; Bu, Yuyu; Ao, Jin-Ping
Abstract: A CuOx /WO3 thin-film based on p-n heterojunction proposed as a highly performance and stable photocathode. The CuOx /WO3 thin-film was deposited by magnetron reactive sputtering layer by layer, followed with slow rate annealing in O2 ambient. This is an excellent method for high-quality and uniform composite thin-film deposition with large areas at a high growth rate. The optimized CuOx /WO3 thin-film photocathode after slow rate annealing at 500 °C in O2 provides an obviously enhanced photoinduced current density of −3.8 mA cm −2 at a bias potential of −0.5 V (vs. Ag/AgCl), which value is 1.5 times higher than that of bared CuOx thin-film. This highly enhanced photoelectrochemical performance is attributed to p-n heterojunction, which accelerates the photogenerated electrons and holes transfer to n-WO3 and p-CuOx, thereby accelerate the separation of photogenerated carries. In addition, WO3 layer covered on the surface of CuOx thin film can improve the stability of Cu2 O in electrolytes. Highlights: CuOx /WO3 photocathode was prepared by magnetron reactive sputtering. Optimization CuOx /WO3 photocathode by annealed at a slow rate. p-n heterojunction improved CuOx /WO3 photocathode.